Burnout Syndrome In The Covid-19 Pandemic And The Virtualization Of Education - Carmen Rosa Mosquera Murillo, Judith Soledad Yangali Vicente, Bellanire Ospina Orejarena, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the research is to determine the relationship between Burnout Syndrome in the framework of the COVID-19 pandemic and the virtualization of education in Colombian official school teachers during the year 2020. The study responds to the mixed approach and sequential design. In its quantitative phase it was deductive-hypothetical, applied, with a non-experimental cross-sectional design, and in its qualitative phase it was inductive, applied with a phenomenological-hermeneutic design. The data collection techniques used were the survey and the interview. The study population consisted of 1093 teachers from official schools in Floridablanca. For the quantitative approach, a non-probabilistic accidental sample of 110 teachers was used, and for the qualitative approach, a non-probabilistic convenience sample of 10 teachers was used. Among the final considerations it can be said that there is an inverse mean correlation between Burnout syndrome and the virtualization of education in this time of the Covid-19 pandemic; it is therefore considered that the effects of the pandemic have maximized the effects of the aforementioned syndrome on educational actors.